The Use of Read, Cover, Remember, Retell (RCRR) Strategy in Improving Students` Reading Achievement - Lestari, Ernia Putri; Abdullah, Umar; Husnaini, Husnaini (Jadila: Journal of Development and Innovation in Language and Literature Education, 2025)
Reading is one of the four important skills that must be taught in English. Reading can help students to understand information better, develop critical skills, and increase vocabulary and understand the content of text. However, the majority of EFL student`s experience difficulty reading widely. This study aimed to determine the impact of the RCRR strategy on the reading achievement of the tenth-grade students at SMA Karya Ibu Palembang. The research used a quasi-experimental design with pretest and posttest non-equivalent groups. The sample consisted of 60 students, with 30 in the experimental group (X.A) and 30 in the control group (X.B). Data were collected through pretests and posttests and analyzed using paired and independent sample t-tests. The paired sample t-test results showed a p-value of 0.000 and a t-value of -55.166, indicating significant improvement in students' reading achievement. The independent sample t-test showed a p-value of 0.000 and a t-value of 3.952, surpassing the t-table value (2.045), proving a significant difference between the groups. The findings confirm that the RCRR strategy positively affects students' reading achievement in descriptive texts, suggesting it is an effective strategy for improving EFL students' reading skills.